Mitochondria-target ubiquinone attenuates bleomycin-induced pulmonary fibrosis - Jiang, Ying; Huang, Zhenghui; Zhou, Ting; Wu, Mi; Zhao, Juan; Xiong, Zheyi; Wang, Rui; Chen, Limin; Weng, Xiufang; Lin, Lan (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis arises from various etiologies, often associated with elevated levels of reactive oxygen species (ROS) stress and activation of pro-fibrotic signaling pathways. The chemotherapeutic drug bleomycin has been shown to exacerbate pulmonary fibrosis during anti-tumor treatment. Further research is needed to combat bleomycin-induced fibrosis.AimThis investigation aims to identify critical mediators of bleomycin-induced pulmonary fibrosis and evaluate the therapeutic potential of mitochondria-targeted ubiquinone (MitoQ) in attenuating fibrotic pathogenesis.MethodsA bleomycin-induced pulmonary injury mouse model and fibroblast cell culture were established, followed by histopathology evaluation, molecule interaction analysis, cytokine quantification, intervention assay, and flow cytometry.ResultsWe analyzed RNA-seq data from a bleomycin-induced pulmonary fibrosis mouse model and identified a network of oxidative stress-related fibrosis genes centered on Tgfb1. In fibroblast cell lines, bleomycin exposure elevated mitochondrial and cellular ROS, increased mitochondrial mass and the MDRlow/MTGhigh cell ratio, downregulated genes linked to ROS scavenging and mitochondrial function, and upregulated transcription of pro-fibrotic molecules. MitoQ effectively reduced mitochondrial ROS, alleviated mitochondrial swelling, and restored transcription of genes involved in mitochondrial redox balance and function. Compared to conventional ubiquinone, MitoQ exhibited significantly greater antifibrotic efficacy, effectively attenuating bleomycin- and TGF-β1-induced fibroblast activation in vitro. In bleomycin-treated mice, MitoQ treatment with markedly suppressed pro-fibrotic molecule transcription and inhibited pulmonary fibrosis progression.ConclusionThese findings not only advance our understanding of the interplay between oxidative stress and pro-fibrotic signaling in bleomycin-induced pulmonary fibrosis but also provide experimental data supporting the use of mitochondria-targeted antioxidant in the treatment of this condition.